Vascular responsiveness measured by tissue oxygen saturation reperfusion slope is sensitive to different occlusion durations and training status - McLay, K. M.; Gilbertson, J. E.; Pogliaghi, S.; Paterson, D. H.; Murias, J. M. (Experimental Physiology, 2016)
The reperfusion rate of near-infrared spectroscopy (NIRS)-derived measures of tissue oxygen saturation (StO2) represent vascular responsiveness. This study examined if the reperfusion slope of StO2 is sensitive to different ischemic conditions (i.e., a dose-response) and if differences exist between two groups of different fitness levels. Nine healthy trained (T; Age: 25 ± 3 yr; VO2max: 63.4 ± 6.7 ml kg-1 min-1) and nine healthy untrained (UT; Age: 21 ± 1 yr; VO2max: 46.6 ± 2.5 ml kg-1 min-1) men performed a series of vascular occlusion tests of different durations (30 s, 1 min, 2 min, 3 min, and 5 min), each separated by 30 min. StO2 was measured over the tibialis anterior using NIRS, with StO2 reperfusion slope calculated as the upslope during 10 s following cuff release. The reperfusion slope was steeper in T compared to UT at all occlusion durations (P < 0.05). For the T group, the reperfusion slope for 30 s and 1 min occlusions were less than all longer durations (P < 0.05). The reperfusion slope following 2 min occlusion was similar to 3 min (P < 0.05) but both were less steep than 5 min of occlusion. In UT, the reperfusion slope at 30 s was smaller than all longer occlusion durations (P < 0.05) and 1 min occlusion resulted in a reperfusion slope that was less steep than following 2 min and 3 min (P < 0.05), albeit not different from 5 min (P < 0.05). The present study demonstrated that the reperfusion rate of StO2 is sensitive to different occlusion durations, and that changes in the reperfusion rate to a variety of ischemic challenges can be used to detect differences in vascular responsiveness between trained and untrained groups.